A textile-based wearable supercapacitor using reduced graphene oxide/polypyrrole composite. (10th May 2019) - Barakzehi, Marjan; Montazer, Majid; Sharif, Farhad; Norby, Truls; Chatzitakis, Athanasios
Abstract: Wearable electronics such as supercapacitors have been extensively explored and developed. Textile-based composites hold excellent promise as suitable hosts for electronic devices for the development of smart garments. In the present work, a textile-based electrode is developed through modification with reduced graphene oxide (rGO) nanosheets and polypyrrole (PPy) nanospherical particles onto polyethylene terephthalate (PET) fabric. The conductive composites are used to fabricate flexible, all-solid-state supercapacitors by using a gel electrolyte. The optimum device delivers an areal capacitance of 0.23 F cm −2 at a scanning rate of 1 mV s −1, a volumetric capacitance of 5.5 F cm −3 at a discharge current density 1.6 mA cm −3, an energy density of 11 μWh cm −2 and a power density of 0.03 mW cm −2 corresponding to 6.86 mg cm −2 of electroactive materials loading. It also retains about 76% of the initial capacitance after 6000 cyclic voltammetric cycles and possesses excellent stability under bending.